Breadcrumb-inspired construction of liquid metal@BN core-shell microparticles for highly thermal conductive elastomeric composites with excellent flexibility and stability. (1st March 2023) - Wang, Zhijian; Li, Jingchao; Ye, Neng; Zhang, Huan; Yang, Dan; Lu, Yonglai
Abstract: The rapid development of wearable electronics urges for flexible thermal management materials with higher service performance and stability of operation under high-complexity environmental stresses. A liquid metal embedded elastomer (LMEE) offers a combined solution with both high flexibility and thermal conductivity to heat dissipation of wearable electronics. But the potential leakage risk of the liquid metal (LM) in LMEE under external force severely limits the application of LMEE in the field of flexible thermal management. Inspired by a traditional Chinese snack, "fried milk", we herein modify the two-dimensional boron nitride (BN) by thiolation, so as to develop LM@BN core-shell particles through the formation of a protective layer around micron-sized LM particles using thiol-metal interactions, before the flexible thermal management material with high stability is finally prepared by the combination between the LM@BN particles and a silicone rubber elastomer. The results demonstrated that the LM@BN core-shell structure can effectively maintain the balance between the tensile property, the thermal conductivity, and the stability of the material, thereby facilitating the future application of LM-elastomer composites with regard to flexible thermal management and thermal interface materials. Graphical abstract: A method based on sulfhydryl-metal coordination interactions is proposed to construct LM@BN core-shell structures for the construction of a highly stable, electrically insulating, flexible thermal management material. Compared with the common liquid metal-embedded elastomer, this method, by introducing a two-dimensional material shell structure, significantly improves the stability of the composite material without liquid metal exudation when it is subjected to pressure, which will significantly broaden the application prospects of liquid metal-elastomer composites in the field of flexible thermal management. Image 1 Highlights: The LM@BN core-shell particles are constructed by sulfhydryl metal interactions between boron nitride and liquid metal. The BN shell gives the LM@BN/PDMS composite excellent stability, avoiding the leakage of liquid metal under pressure. The LM@BN/PDMS composite has excellent flexibility, high thermal conductivity and good electrical insulation property.